KEHIDUPAN SOSIAL ETNIS BATAK DI PESISIR SELATAN (STUDI KASUS DI NAGARI SAGO KABUPATEN PESISIR SELATAN TAHUN 1979-2011 - Gustasari, Vera; Nurhuda, Ahmad; Aziz, Zulkifli (Pendidikan Sejarah, 2014)
Batak communities still exist in Pesisir Selatan region, one of them in Sago village. Batak people who settled in Nagari Sago still run their culture, such as the Protestant religion, have a social organization, whose livelihood is generally uniform and communicate using the language of the Batak in their group. For the problem is formulated as follows: Batak Ethnic Social Life In Pesisir Selatan region (Case Study in Sago Village Pesisir Selatan region from 1979-2011.This research includes the study of history with research methods as follows: (1) heuristic is to look for and collect information from primary and secondary sources, (2) a source of criticism include internal and external criticism, namely by testing for the authenticity of the source or material specified, (3) an interpretation which interprets the activity data that has been collected and (4) the stage of writing a thesis result.The results showed: (1) the ethnic Batak first came to Sago village at 1979. Preceded by Jameal Goison Saragih, Turnip family further. Ethnic Batak more numerous before the earthquake in 2009 and began to decline since the earthquake-occurrence and (2) changes in the social life seen from the interaction with people in villages Sago, occurred in the economic field where visible presence in the field of economic cooperation between the Minangkabau ethnic communities in Sago village and running properly. Ethnic Batak in Sago village have jobs that tend to be uniform, namely trade. Batak ethnic trade done in Sago village is also equal to the characteristic of the Batak ethnic trade in other areas, namely trade cloth and household appliances and use the credit system to its customers. Batak ethnic trade areas not only in Sago village, but most of the Pesisir Selatan region.. The majority of the Batak are Christian Protestant and Christian Catholic and there are also Muslim. In Sago village, ethnic Batak also generally Christian, Muslim ethnic Batak marriage due to the Minang community